2018
DOI: 10.1155/2018/7651482
|View full text |Cite
|
Sign up to set email alerts
|

Tristemma hirtumand Five Other Cameroonian Edible Plants with Weak or No Antibacterial Effects Modulate the Activities of Antibiotics against Gram-Negative Multidrug-Resistant Phenotypes

Abstract: In order to contribute to the fight against infectious diseases, the in vitro antibacterial activity and the antibiotic-potentiating effects of Tristemma hirtum and five other Cameroonian edible plants have been evaluated against Gram-negative multidrug-resistant (MDR) phenotypes. The microdilution method was used to evaluate the bacterial susceptibility of the extracts and their combination to common antibiotics. The phytochemical screening of the extracts was carried out according to standard methods. Phytoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Compounds 1, 4, 5, 9 and 10 are also moderately active (MIC from 16 to 64 µg/mL) and then, could justify the activity shown by the original fraction, suggesting that many of them should proceed by synergism to enable the higher activity of the extract. This potentiating effect of the methanol extract from leaves of T. hirtum against Multi-Drugs Resistant Gram-Negative Bacteria have been reported when it was combined with other antibiotics [16]. Compound 5 as a substrate of prenylation reaction showed moderate activity against three bacteria strains tested while two of its semi-synthetic derivatives, 5a and 5c showed the same activity against four various bacterial strains.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Compounds 1, 4, 5, 9 and 10 are also moderately active (MIC from 16 to 64 µg/mL) and then, could justify the activity shown by the original fraction, suggesting that many of them should proceed by synergism to enable the higher activity of the extract. This potentiating effect of the methanol extract from leaves of T. hirtum against Multi-Drugs Resistant Gram-Negative Bacteria have been reported when it was combined with other antibiotics [16]. Compound 5 as a substrate of prenylation reaction showed moderate activity against three bacteria strains tested while two of its semi-synthetic derivatives, 5a and 5c showed the same activity against four various bacterial strains.…”
Section: Discussionsupporting
confidence: 58%
“…It is widely found in the West Region of Cameroon where it is used in folk medicine, associated with other plants for the treatment of hemorrhoids, reproductive problems, skin diseases and typhoid fever [14,15]. Previously, researchers have reported antibacterial activities of Tristemma hirtum extracts [16]. As part of our ongoing phytochemical studies of medicinal plants growing in Cameroon, we have previously reported the isolation and characterization of ten compounds including flavonoids, terpenoids, glycerol derivatives and hydrolysable tannins from some fractions of the methanol extract from Tristemma hirtum [17].…”
Section: Introductionmentioning
confidence: 99%
“…The search for new molecules to tackle bacterial antibio-resistance has become imperative. Plant kingdom has a great number of bioactive substances, and good numbers of medicinal plants from the flora of Cameroon have proven their ability to inhibit the growth of Gram-negative bacteria, including MDR phenotypes [5][6][7][8][9]. C. sieberiana (Caesalpiniaceae) is widespread in West Africa and is very common in all savannah woodlands or shrubs of the Sudanian zones up to the edge of the Guinean forest in Casamance.…”
Section: Introductionmentioning
confidence: 99%
“…and analgesic properties. [2][3] Also, flavonol glycosides, β-sitosterol glucopyranoside and terpenoid acids have been isolated from the ethyl acetate and n-butanol soluble fractions of the plant methanol extract. 4 In addition, phytocompounds such as alkaloids, triterpenes, steroids, flavonoids and polyphenols were identified in the methanol leaf extract of the plant.…”
mentioning
confidence: 99%
“…4 In addition, phytocompounds such as alkaloids, triterpenes, steroids, flavonoids and polyphenols were identified in the methanol leaf extract of the plant. 3 However, numerous biological activities have been reported for other species of this family including antioxidant, antihypertensive, antimicrobial, cytotoxic, hemostatic, antiinflammatory and antihyperglycemic properties. [4][5][6] Also, flavonoids, polyphenols, steroids, fatty acids, etc have been identified from members of this family.…”
mentioning
confidence: 99%